2006
DOI: 10.1107/s1600536806013407
|View full text |Cite|
|
Sign up to set email alerts
|

1-Acetyl-3-ethyl-r-2,c-6-di-2-furylpiperidin-4-one

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean (C-C) = 0.004 Å R factor = 0.048 wR factor = 0.166 Data-to-parameter ratio = 13.4For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The conformation of (I) was established by 1 H and 13 C NMR sepectroscopy by Manimekalai & Rajarajan, 1996;Pandiarajan, et al, 2000. Balamurugan et al, 2006 have reported crystal structures of di-2-furylpiperidin-4-one derivatives, wherein the piperidine ring adopts a chair and a twist-boat conformations respectively.…”
Section: S1 Commentmentioning
confidence: 99%
“…The conformation of (I) was established by 1 H and 13 C NMR sepectroscopy by Manimekalai & Rajarajan, 1996;Pandiarajan, et al, 2000. Balamurugan et al, 2006 have reported crystal structures of di-2-furylpiperidin-4-one derivatives, wherein the piperidine ring adopts a chair and a twist-boat conformations respectively.…”
Section: S1 Commentmentioning
confidence: 99%
“…The title compound, (I), has been analysed as part of our crystallographic studies on substituted piperidines (Balamurugan, et al, 2006). The present X-ray diffraction study was undertaken to determine how the conformation of the system is affected by the substitution of an acetyl group at N, furyl rings at positions 2 and 6 and methyl groups at positions 3 and 5 of the piperidin-4-one.…”
Section: Commentmentioning
confidence: 99%
“…For related literature, see: Lavagnino & Shepard (1957); Balamurugan et al (2006Balamurugan et al ( , 2007. Balamurugan et al (2006Balamurugan et al ( , 2007 have reported crystal structures of di-2-furylpiperidin-4one derivatives, where the piperidine ring adopts chair and twist-boat conformations. independent and constrained refinement Á max = 0.27 e Å À3 Á min = À0.24 e Å À3 Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%